A Search for High-Mass Stars Forming in Isolation using CORNISH and ATLASGAL - Tremblay, C.; Walsh, Andrew; Longmore, S.; Urquhart, J.; König, C. (2015)
Theoretical models of high-mass star formation lie between two extreme scenarios. At one extreme, all the mass comes from an initially gravitationally bound core. At the other extreme, the majority of the mass comes from cluster scale gas, which lies far outside the initial core boundary. One way to unambiguously show high-mass stars can assemble their gas through the former route would be to find a high-mass star forming in isolation. Making use of recently available CORNISH and ATLASGAL Galactic plane survey data, we develop sample selection criteria to try and find such an object. From an initial list of approximately 200 sources, we identify the high-mass star-forming region G13.384 + 0.064 as the most promising candidate. The region contains a strong radio continuum source, that is powered by an early B-type star. The bolometric luminosity, derived from infrared measurements, is consistent with this. However, sub-millimetre continuum emission, measured in ATLASGAL, as well as dense gas tracers, such as HCO+(3–2) and N2H+(3–2) indicate that there is less than ~ 100 M? of material surrounding this star. We conclude that this region is indeed a promising candidate for a high-mass star forming in isolation.